2013
DOI: 10.3390/rs5126938
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Satellite Detection of Post-Fire Vegetation Trends in Boreal Forests of China

Abstract: This paper describes the long-term effects on vegetation following the catastrophic fire in 1987 on the northern Great Xing'an Mountain by analyzing the AVHRR GIMMS 15-day composite normalized difference vegetation index (NDVI) dataset. Both temporal and spatial characteristics were analyzed for natural regeneration and tree planting scenarios from 1984 to 2006. Regressing post-fire NDVI values on the pre-fire values helped identify the NDVI for burnt pixels in vegetation stands. Stand differences in fire dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
0
23
0
4
Order By: Relevance
“…While forest/non-forest types were fairly discriminated, detailed tree species composition cannot be effectively extracted because of their spectral similarity. With vegetation indices, various studies reported that greenness of boreal forests can grow back to pre-fire conditions in 5-20 years depending on fire severities and imagery resolutions [9,10,19]. This study revealed, however, that Xing'an larch re-composition had not been fully recovered in a 30-year span.…”
Section: The Nbr Fire Intensity Map and Xing'an Larch Re-compositionmentioning
confidence: 73%
See 4 more Smart Citations
“…While forest/non-forest types were fairly discriminated, detailed tree species composition cannot be effectively extracted because of their spectral similarity. With vegetation indices, various studies reported that greenness of boreal forests can grow back to pre-fire conditions in 5-20 years depending on fire severities and imagery resolutions [9,10,19]. This study revealed, however, that Xing'an larch re-composition had not been fully recovered in a 30-year span.…”
Section: The Nbr Fire Intensity Map and Xing'an Larch Re-compositionmentioning
confidence: 73%
“…mongolica). Other deciduous species such as aspen and willow and coniferous species such as spruce only grow in less than 10% of the region [9]. As Xing'an larch is the primary concern of this study, these tree species are not examined to avoid unnecessary classification uncertainties.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations